2017
DOI: 10.7324/japs.2017.70904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on Hydnophytum formicarum Tuber from Setiu Wetland (Malaysia) and Muara Rupit (Indonesia) for Antibacterial and Antioxidant activities, and anti-cancer Potency against MCF-7 and HeLa Cells

Abstract: This current study is to evaluate and compare the antibacterial, antioxidant and anticancer activity of H. formicarum tubers from Setiu Wetland, Terengganu, Malaysia and inland forest of Muara Rupit, SumateraSelatan, Indonesia. The tubers were extracted using methanol and then sequentially fractioned using solvent partitioning by n-hexane, dichloromethane, and ethyl acetate. The phytochemical study showed that samples from both places possessed same phytochemicals content that was rich with phenols, tannins, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Research using H. formicarum tuber extract from different locations (Setiu Wetland-Malaysia and Muara Rupit-Indonesia) showed that H. formicarum tuber extract from Setiu Wetland had very strong cytotoxic activity against MCF-7 (human breast cancer cell line with estrogen, progesterone, and glucocorticoid receptors) compared with H. formicarum from Muara Rupit. However, both of them did not show any cytotoxic activity against HeLa cells [43].…”
Section: Sarang Semut (Ant Nest)mentioning
confidence: 88%
“…Research using H. formicarum tuber extract from different locations (Setiu Wetland-Malaysia and Muara Rupit-Indonesia) showed that H. formicarum tuber extract from Setiu Wetland had very strong cytotoxic activity against MCF-7 (human breast cancer cell line with estrogen, progesterone, and glucocorticoid receptors) compared with H. formicarum from Muara Rupit. However, both of them did not show any cytotoxic activity against HeLa cells [43].…”
Section: Sarang Semut (Ant Nest)mentioning
confidence: 88%
“…Namun pada beberapa jurnal lain, pasir kuarsa dapat digunakan untuk pemurnian [11]. [15]. Hal ini mengakibatkan pembentukan lapisan sel tidak terbentuk secara utuh.…”
Section: Pendahuluanunclassified